Fully‐Textile Seam‐Line Sensors for Facile Textile Integration and Tunable Multi‐Modal Sensing of Pressure, Humidity, and Wetness. Issue 8 (5th June 2020) - Agcayazi, Talha; Tabor, Jordan; McKnight, Michael; Martin, Isaac; Ghosh, Tushar K.; Bozkurt, Alper
Abstract: The unique potential of e‐textiles for unobtrusive and ubiquitous monitoring and their innovative interfacing with electronic devices has garnished great attention. Sensors are one of the few essential devices or components necessary for most functional e‐textile applications. Ideally, any e‐textile based sensor should be soft, easily integrated in textile manufacturing processes, and tunable for the desired applications. Here, an easy‐to‐manufacture, tunable, fully‐textile sensor system with capability of detecting pressure, humidity, or wetness is presented. Capacitive pressure sensors are formed via a traditional sewing process with two commercially available conductive sewing yarns (silver‐plated polyamide (silver) and stainless steel (SS)) with cotton knit, polyethylene‐terephthalate (PET) knit and elastomeric meltblown textile dielectrics. The relationship between the sensor's physical, mechanical, and electromechanical properties including hysteresis, sensitivity, response, and relaxation time is evaluated. In addition, the same sensor configuration is assessed for its humidity and wetness sensing performance. Results indicate that pressure, relative humidity (RH), and wetness sensing performance are easily tunable using different combinations of the conductive and dielectric textile materials. Finally, proof of concept deployment demonstrations as human‐machine interfaces within a pressure sensing mat and a smart glove capable of remotely controlling a drone are provided. Abstract : An easy‐to‐manufacture, tunable, fully‐textile sensor system capable of detecting pressure, humidity, or wetness is presented. Capacitive sensors are fabricated via sewing and results indicate that sensor performance can easily be tuned using different conductive yarns and textile dielectric materials. Proof of concept demonstrations are provided including a pressure‐sensing mat and a smart glove capable of remotely controlling a drone.